Penyelesaian Perselisihan dalam Praktik Kedokteran Mengacu pada Undang-Undang Kesehatan 2023 - Idris, Berlian; Prastopo; Prasetyo, Boedi (LPPM Universitas Terbuka, 2024)
Dispute can occur in medical practice if patient(s) feel their interests are being damaged or they received results not as expected. This study is a normative, qualitative research using secondary data on dispute resolution in accordance to Act Number 17 Year 2023 on Health, compared to before the Law was enacted. According to the Act, patients or their representatives who felt aggrieved can report the doctor(s) to Professional Disciplinary Council, to the authorities for suspected criminal act, and/or to the court for civil act violation. The Council’s recommendation that states there is a violation on current standards is required for criminal investigation to proceed, and for civil lawsuit to go to court. Such requirement is nonexistent in Act Number 29 Year 2004 on Medical Practice. This could be observed in the case of dr. Dewa Ayu Sasiary Prawan, et al in 2010 where patient Mrs. Julia Fransiska Makatey that they treated was deceased. They were found not guilty in district court, sentenced to imprisonment in Supreme Court cassation, and finally ruled not guilty in Supreme Court judicial review verdict because no proven standard violations. Learning from this, such Council that has utmost integrity and works profesionally is needed for a fair dispute resolution.